Highways and Growth : A Causal Analysis for India - Panda, Prerna; Mishra, Shibani (Arthshastra Indian Journal of Economics & Research, 2018)
The paper investigated the relationship between the growth of highways and economic growth. We tested for mutual causality between the growth of road networks (which were functionally divided as state highways and national highways) and growth in investment and GDP. We employed time series data set containing observations of growth in road route kilometres by type for India over the period from 1972 - 2016 to fit a vector autoregressive model with exogenous variable describing the growth in road networks, GDP, and gross capital formation. We also checked if the establishment of National Highway Authority of India (NHAI) had any significant impact on the economy. The results indicated the existence of bidirectional causality between growth in GDP and growth in national highways and a unidirectional causality was seen from growth in national highways to growth in gross capital formation. Additionally, it was observed that the growth in state highways led to subsequent growth in national highways as well. The NHDP programme had a significant impact on the expansion of national highways, but no causal influence could be empirically identified on GDP and gross capital formation.